Mental stress post-COVID-19 - Zafir Khan Mohamed Makhbul; Zainab Rawshdeh (International Journal of Public Health Science (IJPHS), 2021)
Coronavirus disease (COVID-19) that is plaguing the world today surely carves a dark, unforgettable history. It has been declared a global pandemic by the World Health Organization (WHO). This shows that it has spread worldwide, transcending every border, and then finally penetrating every corner of the world. Despite its small size (measured in nanometer), its influence is great enough in triggering stress. As various countries declare a state of Emergency, restricted movement order and lockdown, varying reactions like sorrow, anxiety, misperception and fear have been ignited in the society. All of these have cumulatively caused stress among them. This current review paper summarizes and discusses the published literature addressing mental health concerns linked to the COVID-19 pandemic. Studies show that excessive stress causes the failure in the individual’s mental and physical systems. The issue here is how the situation at the workplace, post-COVID-19 is different from the previous situation. Thus, the psychological preparation of every member in the organization is crucial to face the challenges coming their way. The available literature showed consensus that the COVID-19 pandemic not only affects physical health, but also stress and well-being. In conclusion, emotional well-being must be emphasized through training and human resource development strategy to prepare and empower the mentality of the organizational members to address this stress.